Decision support system model for selection of best formula milk for toddlers using fuzzy multiple attribute decision making - Ristiani; Pardimin; Teh K.S.M.; Fauzi A.; Hananto A.L.; Huda M.; Muslihudin M.; Shankar K.; Maseleno A. (Institute of Advanced Scientific Research, Inc., 2023)
According to national objectives, the mortality rate of Toddler is expected to be reduced. The increase of toddler mortality rate is often caused by lack of nutrition in toddler. One way to reduce toddler mortality is by encouraging mothers to provide the right formula milk for their toddlers. Toddler is a group of people who is prone to nutritional problems. In the Toddlers time the process of body growth and development is very rapid that it requires a sufficient and adequate supply of food and nutrition. When the occurrence of malnutrition in childhood can cause growth disorders, mental development disorders, and increased mortality. This paper was discussed how to overcome the problems in the selection of Formula Milk for proper nutrition of toddler, so that the results given more accurate. So it can provide a positive response for every Toddler in Formula Milk to meet the needs of toddler Nutrition. The method used was Fuzzy Multiple Attribute Decision Making (FMADM) method of simple additive weighting (SAW), this method was chosen because it can choose the best alternative from a number of alternatives, in this case the alternative is to determine the formula milk based on the specified criteria. The calculation of SAW was to determine the priority weight of choice depends on the score of the criteria and sub criteria, then the criteria and sub criteria will provide the priority to determine the desired Formula Milk in providing adequate nutrient intake in the growth process of each Toddler by consuming formula milk as a standard to meet the need of Toddlers life. 2018, Institute of Advanced Scientific Research, Inc.. All rights reserved.